Isolated tricuspid valve infective endocarditis with multiple septic pulmonary emboli in a patient with atopic dermatitis. Issue 2 (27th December 2020) - Shioya, Nobuki; Inoue, Nozomu; Miyano, Erina; Nakayama, Miyabi; Tsukamoto, Yuki; Hazama, Koji; Shichinohe, Yasuo
Abstract: Multiple lung nodules in atopic dermatitis patients may reflect infective endocarditis. Our case underlines the importance of potentially severe infections due to staphylococci associated with atopic dermatitis. Abstract : Multiple lung nodules in atopic dermatitis patients may reflect infective endocarditis. Our case underlines the importance of potentially severe infections due to staphylococci associated with atopic dermatitis.